2005
DOI: 10.1007/s10681-005-2526-y
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for increasing heterozygosity in crops: Vicia faba mating system as a study case

Abstract: Our research assesses the feasibility of using artificial selection on pre-mating floral traits to modify the mating system of faba bean (Vicia faba). This analysis considered two synthetic populations, which were derived from different genetic pools and had undergone five years of multiplication. For these populations, we identified floral and inflorescence traits that influence outcrossing per plant and examined the relative importance of these traits in governing yield. Codominant isozyme loci and the mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 53 publications
(50 reference statements)
0
30
0
Order By: Relevance
“…This can be overcome by increasing recombination through the use of male sterility when available [63], or cisgenesis [13], or by genetic manipulation of flower biology [64][65][66][67].…”
Section: Evolutionary Plant Breedingmentioning
confidence: 99%
“…This can be overcome by increasing recombination through the use of male sterility when available [63], or cisgenesis [13], or by genetic manipulation of flower biology [64][65][66][67].…”
Section: Evolutionary Plant Breedingmentioning
confidence: 99%
“…Varieties developed through mass selection would also have considerable genetic variation because several similar looking plants which are variable for quantitative traits are selected and bulked (Singh, 2002). For instance, the development of synthetic varieties has been effective for increasing yield and stability in faba bean (Vicia faba L.) because heterozygosity is enhanced while at the same time the dangers of genetic vulnerability from varietal uniformity is reduced (Suso et al, 2005). A work in Kenya clearly showed that deliberately maintaining some level of variation in varieties turned out to be an important prerequisite of high grain yield in sorghum grown under drought stress (Haussmann et al, 2000).…”
Section: Maintaining Broad Genetic Base In Varietiesmentioning
confidence: 99%
“…DIAS of traits, such as standard length, width, area, and perimeter, facilitates extensive and detailed phenotypic analyses to describe subtle differences in flower size (Yoshioka et al 2004(Yoshioka et al , 2005. Appropriate software packages can provide more accurate, consistent, and objective measurement for floral traits, such as style length, ovary style angle (for assessment of the mechanical fit to pollinator) or pollen presentation that were impossible or impractical to determine manually (Suso et al 2005a).…”
Section: Key Aspects Of Floral Traits For Improving Cprmentioning
confidence: 99%
“…Studies on faba bean have been focused on the analysis of out-crossing within cultivars (Suso et al 2001), and pollen-mediated gene flow between cultivars. Breeding questions include the choice of appropriate procedures for cultivar development that exploit heterosis and maximize yield stability (Metz et al 1993Pierre et al 1996;Carre et al 1998;Suso et al 2005a), and for maintenance of varietal and germplasm purity during seed multiplication .…”
Section: Vicia Faba Lmentioning
confidence: 99%
See 1 more Smart Citation